Membrane Vesicle Production as a Bacterial Defense Against Stress - Mozaheb, Negar; Mingeot-Leclercq, Marie-Paule (Frontiers in Microbiology, 2020)
Membrane vesicles are the nano-sized vesicles originating from membranes. The production of membrane vesicles is a common feature among bacteria. Depending on the bacterial growth phase and environmental conditions, membrane vesicles show diverse characteristics. Various physiological and ecological roles have been attributed to membrane vesicles under both homeostatic and stressful conditions. Pathogens encounter several stressors during colonization in the hostile environment of host tissues. Nutrient deficiency, the presence of antibiotics as well as elements of the host’s immune system are examples of stressors threatening pathogens inside their host. To combat stressors and survive, pathogens have established various defensive mechanisms, one of them is production of membrane vesicles. Pathogens produce membrane vesicles to alleviate the destructive effects of antibiotics or other types of antibacterial treatments. Additionally, membrane vesicles can also provide benefits for the wider bacterial community during infections, through the transfer of resistance or virulence factors. Hence, given that membrane vesicle production may affect the activities of antibacterial agents, their production should be considered when administering antibacterial treatments. Besides, regarding that membrane vesicles play vital roles in bacteria, disrupting their production may suggest an alternative strategy for battling against pathogens. Here, we aim to review the stressors encountered by pathogens and shed light on the roles of membrane vesicles in increasing pathogen adaptabilities in the presence of stress-inducing factors.